Prayers and the construction of Israelite identity (Ancient Israel and its literature ;, 2019)
This collection of essays from an international group of scholars focuses on how biblical prayers of the Persian and early Hellenistic periods shaped identity, evoked a sense of belonging to specific groups, and added emotional significance to this affiliation. Contributors draw examples from different biblical texts, including Genesis, Samuel, Kings, Chronicles, Ezra and Nehemiah, Psalms, Jonah, and Daniel.